2007
DOI: 10.1128/mcb.00702-07
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Dependence of Chromosomal R-Loops at the Immunoglobulin Heavy-Chain Sμ Class Switch Region

Abstract: The mechanism by which the cytidine deaminase activation-induced deaminase (AID) acts at immunoglobulin heavy-chain class switch regions during mammalian class switch recombination (CSR) remains unclear. R-loops have been proposed as a basis for this targeting. Here, we show that the difference between various forms of the S locus that can or cannot undergo CSR correlates well with the locations and detectability of R-loops. The S R-loops can initiate hundreds of base pairs upstream of the core repeat switch r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 45 publications
4
101
0
Order By: Relevance
“…It is important to note that until now it was not fully understood what the conditions for R-loops formations were. A couple of recent studies have suggested that R-loops are initiated from 50-bp-long regions, which contain the motif GGGGC TGGGG and comprise at least 50% Gs (Huang et al 2007;Roy et al 2008). We found ∼300 genes that, in their first 1000 bp, contain such regions.…”
Section: Localization Of Mutationsmentioning
confidence: 60%
“…It is important to note that until now it was not fully understood what the conditions for R-loops formations were. A couple of recent studies have suggested that R-loops are initiated from 50-bp-long regions, which contain the motif GGGGC TGGGG and comprise at least 50% Gs (Huang et al 2007;Roy et al 2008). We found ∼300 genes that, in their first 1000 bp, contain such regions.…”
Section: Localization Of Mutationsmentioning
confidence: 60%
“…The fraction of substrate that forms an R-loop exhibits a mobility difference and runs more slowly than the double-stranded DNA substrate, even on these linear substrates (7). We and others have demonstrated that the DNA in the shifted position is R-looped, based on RNase H1 sensitivity and sodium bisulfite chemical probing for single strandedness (12,31,43).…”
Section: Resultsmentioning
confidence: 93%
“…Given that AID requires single-stranded DNA, a key question concerns how any single strandedness is exposed within the switch regions (33). We have shown that R-loops are detectable at the S␥3 and S␥2b acceptor switch regions (13,43) and, more recently, at the S switch regions (12). These R-loops can be kilobases in length and provide a ready target for AID at any of the C's within the top strand.…”
mentioning
confidence: 99%
“…To explore the mechanism by which AID-mediated Top1 reduction augments S region cleavage and CSR, we speculated that aberrant supercoiling by Top1 protein reduction may induce non-B DNA structure in the S region so that Top1 cannot religate, resulting in irreversible cleavage by Top1. DNA structural alterations can be estimated by the DNA's sensitivity to bisulfite modification from dC to dU, which occurs in the single-stranded regions (6,7). The presence of consecutive C bases is suitable for determining the single-strandedness by the bisulfite assay (7).…”
Section: Top1mentioning
confidence: 99%
“…The S region transcripts seem to remain on the DNA template for a short period, thus facilitating the formation of R-loop. Lieber and colleagues reported that the bisulfite treatment of nuclear DNA from switch-induced spleen cells converted dC to dU in the S region, indicating the presence of single stranded DNA in the S region in activated B cells (6,7). R-loop may not survive long but lead to the formation of non-B structures including stem-loop, cruciform, and triplex in the S region because of abundant inverted repeats (3,(8)(9)(10).…”
mentioning
confidence: 99%